DINAMIKA HARGA DAN MARJIN PEMASARAN BERAS PADA PASAR BERAS INDONESIA - Desi Aryani; Ronnie Susman Natawidjaja; Trisna Insan Noor; Andy Mulyana (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2017)
in Indonesia as well as examine the causes of these changes. The method used in this research is the empirical method that uses statistical and econometric analysis tool in the classification of time series models. Data are obtained from the Central Bureau of Statistics, the secondary data are monthly data of dry milled grain price in producer level and rice price in consumer level from 2008 to 2015. The analysis showed the rice price that uses real price data both at the level of producer and consumer are showed an upward trend. It means beside inflation, there is another factor that caused the rising of rice prices. The rice price in Indonesia tends to increase every year, it is also seemed to fluctuate over time, with a larger price fluctuations at the farm level than consumer level. The rice price in producer and consumer level did not move with the same pattern in 2014, this led to the difference marketing margins among the time. Differences rice marketing margin is due to the structure of the rice market in Indonesia is imperfectly competitive market or tend to oligopsony / oligopoly, in the market of rice trader is a price maker while